2010
DOI: 10.1891/0889-8391.24.4.314
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cognitive Interventions in Treating Depressed Breast Cancer Patients

Abstract: In behavioral medicine, there is adequate support for behavior modification strategies in reducing depression and anxiety in medical patients. There is comparably less support for cognitive interventions with these patients. Treatment outcome studies with cancer patients generally support the efficacy of cognitive-behavioral interventions, but studies have significant methodological limitations. Additionally, cognitive-behavioral therapy for depression incorporates numerous treatment components, and when exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Possible scores range from zero to 54, and higher scores are indicative of more severe depression. The HRSD has been used to measure depression in breast cancer patients (Hopko & Colman, 2010; Savard et al, 2006; Park, Lee, Kim, Bae, & Hahm, 2012). It has been found to be a valid and reliable measure in one study of cancer patients (Olden, Rosenfeld, Pessin, & Breitbar, 2009) and has shown good sensitivity, specificity, and predictive validity in another sample of patients with various cancer types (Hopko et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Possible scores range from zero to 54, and higher scores are indicative of more severe depression. The HRSD has been used to measure depression in breast cancer patients (Hopko & Colman, 2010; Savard et al, 2006; Park, Lee, Kim, Bae, & Hahm, 2012). It has been found to be a valid and reliable measure in one study of cancer patients (Olden, Rosenfeld, Pessin, & Breitbar, 2009) and has shown good sensitivity, specificity, and predictive validity in another sample of patients with various cancer types (Hopko et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Research evidence suggests that cognitive behavioural therapy (CBT) is effective for people with LTCs regarding both psychological and physical measures, e.g. in pain management (Gatchel, Peng, Peters, Fuchs and Turk, 2007; Morley, Eccleston and Williams (1999); oncology (Hopko and Colman, 2010); and in diabetes management (Ismail, Winkley and Rabe-Hesketh, 2004). However, much of this work focuses on issues such as education of the condition, adjustment, adherence, relationship issues, as well as on depression/anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing body of evidence that supports the use of adapted CBT across a range of LTCs (Sage, Sowden, Chorlton and Edeleanu, 2008) and MUS (Deary, Chalder and Sharpe, 2007). Specific examples in LTC include CBT for type-2 diabetes (Ismail, Winkley and Rabe-Hesketh, 2004; Wroe, Rennie, Gibbons, Hassy and Chapman, 2015), oncology (Hopko and Coleman, 2010) and multiple sclerosis (Moss-Morris and Wearden, 2013). In MUS, randomized control trials (RCT) in irritable bowel syndrome (Moss-Morris, McAlpine, Didsbury and Spence, 2010) and chronic fatigue (Chalder, Wallace and Wessley, 1997) demonstrate efficacy and particularly the use of pacing as a helpful technique.…”
Section: Introductionmentioning
confidence: 99%